Assessing the European Union's Assistance to Civil Society in Its Eastern Neighbourhood: Lessons from the South Caucasus. Issue 1 (2nd January 2016) - Aliyev, Huseyn
Abstract: Since the fall of the Soviet Union, assistance to civil society has been at the forefront of the European Union's (EU) strategy in its post-Soviet Eastern neighbourhood. The literature on the EU support to civil society in post-Soviet countries has so far primarily focused on democratisation and the research assessing the effects of EU assistance to civil society has been limited. This study builds on existing literature about the EU cooperation with civil society in the South Caucasus by focusing on the following question. How successful were the EU's efforts in supporting civil society in the South Caucasus so far? By relying on a combination of qualitative elite interviews and secondary sources, this article assesses the impact of the key EU initiatives and programmes implemented in the South Caucasus during the past two decades. It is concluded here that despite steady improvements of EU policies and approaches of empowering civil actors in the region, the European Union's assistance to civil society in the South Caucasus region remains inconsistent and limited.